Kebebasan Hak Ijtihad Nikah Beda Agama Pasca Putusan Mahkamah Konstitusi - Tobroni, Faiq (Mahkamah Konstitusi Republik Indonesia, 2015)
This paper has three key issues. The first issue discusses the arguments constructed by applicant of judicial review (JR) to assess the constitutional rights’ violations caused by the application of Article 2 (1) UUP. The second issue discusses on how the Constitutional Court (MK) seated position of state associated marital affairs in the rejection of JR. The third issue discusses model of freedom of ijtihad (legal thought) on interfaith marriage as the impact of MK’s Decision. Based on the discussion, regarding to the first issue, the applicant of JR assess the application of Article 2 (1) UUP has legitimized the state as the sole interpreters of religious teachings for a requirement validity of the marriage. According to the applicant, the role is used by the state (The Office for Religious Affairs/KUA) to not accept interfaith marriage. This refusal led to the violation of some other constitutional rights. Furthermore, as the findings of the second issue, MK’s decision has placed the real position of state not as interpreters of religious teachings, but merely to accommodate the results of religious scholars’s ijtihad regarding marriage into the state law. Thus, it is not true that the state has violated the constitutional right to more intervene the religious life of citizens. Last findings as the third issue, MK’s decision has affected the model of ijtihad freedom on interfaith marriage. Actually interfaith marriage can still be served through the Civil Registry Office (KCS). KCS could be an alternative way to facilitate the interfaith marriages for all religions in Indonesia. Special for KUA, the institution reject to record interfaith marriage. In this way, it only accommodates freedom of ijtihad within the limits of ijtihad jama’i. KUA just accomodates ijtihad by institutions such as the Majelis Ulama Indonesia, Nahdlatul Ulama, Muhammadiyah and other similar institutions that reject interfaith marriage. Special for marriage in muslim community, ijtihad jama’i is better than ijtihad fardiy because the second could trigger the liberalization of marriage laws (temporary marriages, polygamy more than four, underage marriages and denial of recording).